2022
DOI: 10.17219/dmp/150831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral antiseptics on the viral load of SARS-CoV-2: A randomized controlled trial

Abstract: Background. In the oral cavity, which plays an important role in the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), it is possible to reduce the viral load of SARS-CoV-2 with antiseptics, thereby minimizing the transmission of the virus during dental procedures.Objectives. The aim of this study was to clinically evaluate the effect of the hypochlorous acid (HClO) and povidone-iodine (PVP-I) solutions on the oral viral load of SARS-CoV-2.Material and methods. This randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Out of these, three clinical studies were eligible for quantitative analysis [27] , [28] , [29] . The reasons for exclusion after full-text screening are reported in Table 3 [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these, three clinical studies were eligible for quantitative analysis [27] , [28] , [29] . The reasons for exclusion after full-text screening are reported in Table 3 [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] .…”
Section: Resultsmentioning
confidence: 99%
“… Off-topic 4 [32] , [35] , [45] , [49] 4. No longitudinal data on SARS-CoV-2 viral load in human oropharyngeal fluids and surrogates 11 [54] , [56] , [57] , [58] , [66] , [67] , [68] , [70] , [80] , [83] , [87] 5. Investigation/use of viruses or pseudoviruses different from SARS-CoV-2 5 [50] , [51] , [52] , [77] , [81] 6.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [ 11 , 16 18 , 21 , 23 , 24 ] reported the intervention effect of mouthwash on the CT value of novel coronavirus, with 260 cases in the treatment group and 145 cases in the control group. The fixed effects model (I 2 = 10.3%, P = 0.316) was used to pool the effect size, and the analysis results showed a positive effect in terms of CT value of novel coronavirus [SMD = 0.35, 95% CI (0.21, 0.50)] in the mouthwash group compared with the control group as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 shows all the povidone-iodine RCTs in COVID-19, studying several other outcomes in addition to mortality (hospitalization, recovery, viral positivity, viral load, symptomatic cases, both in early and in late treatments): Figure 8. Random effects meta-analysis for all RCTs about povidone-iodine in COVID-19 [100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117]. This plot shows pooled effects, see the specific outcome analyses for individual outcomes, and the heterogeneity section [21] for discussion.…”
Section: Povidone-iodine (And Other Antiseptics For Local Use)mentioning
confidence: 99%